2002
DOI: 10.1203/00006450-200201000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Functional Development of Fat Absorption in Term and Preterm Neonates Strongly Correlates with Ability to Absorb Long-Chain Fatty Acids from Intestinal Lumen

Abstract: Our goal for this study was to determine whether the maturation of fat absorption in neonatal life is functionally related to an increased ability to hydrolyze dietary fat, to absorb long-chain fatty acids, or to do both. In 16 preterm and in eight term neonates, the intestinal ability to hydrolyze triacylglycerols and the capacity to absorb long-chain fatty acids were determined at several times between birth and 5 mo after the term age. These processes were compared with the percentage of fat absorption (for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
39
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 42 publications
1
39
1
Order By: Relevance
“…The median stool excretion of labelled ALNA (7%) is comparable to that of previous studies in term and pre-term infants using different methods (10,11). Although as a group, these infants appear to absorb ALNA well, availability varied widely with the poorest absorption in the most premature.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The median stool excretion of labelled ALNA (7%) is comparable to that of previous studies in term and pre-term infants using different methods (10,11). Although as a group, these infants appear to absorb ALNA well, availability varied widely with the poorest absorption in the most premature.…”
Section: Discussionsupporting
confidence: 79%
“…Fat absorption is believed to be related to the maturity of the gastrointestinal tract in the pre-term neonate. Rings et al demonstrated improving absorption of stearic and palmitic acid between 32 wk and 54 wk postconceptual age (10). As regards long chain polyunsaturated fatty acids, Moya and coworkers reported that the absorption of ALNA was relatively high (Ͼ90%), but the absorption of DHA was considerably less (ϳ62%) and more variable (11).…”
mentioning
confidence: 99%
“…They stress the importance of the lipid composition of nutrition for postnatal development (see Refs. [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…The observations by Rings et al (2) raise the interesting notion that there are limiting functions in the enterocyte previously assumed to be passive, that impact or limit the postprandial response to dietary fat and are related to a variety of interorgan pathways of lipid transport and major disease associated processes (e.g., Clearance of lipoprotein remnant particles). Thus, it is likely that the observations of Rings et al (2) and further investigation of enterocyte functions responsible for processing of dietary fats will lead to a broad impact on our understanding of the implications of changes in fat absorption during more than just the neonatal period of life.…”
mentioning
confidence: 99%
“…Thus, it is likely that the observations of Rings et al (2) and further investigation of enterocyte functions responsible for processing of dietary fats will lead to a broad impact on our understanding of the implications of changes in fat absorption during more than just the neonatal period of life.…”
mentioning
confidence: 99%